The Impact of Capabilities, Business Models, and Digital Transformation on UMKM Performance: The Mediation Role of Strategic Partnership - Edi, Ragil Yoga; Arafah, Willy; Tanuwijaya, Justine (Journal of Social Science and Business Studies, 2025)
This study investigates the influence of capabilities, business models, and digital transformation on the success of MSMEs, with strategic partnerships functioning as a mediating factor. The research utilizes survey data from 247 MSME entrepreneurs and managers in Jakarta who have integrated digital platforms into their business operations. The collected data is analyzed using PLS-SEM. The findings reveal that business models, digital transformation, and strategic partnerships significantly impact SME performance in Jakarta. Strategic partnerships serve as a crucial intermediary, linking business models and digital transformation to corporate performance and amplifying their effect. In contrast, the broader relationship involving capabilities exhibits minimal influence on performance, either directly or through the mediation of strategic partnerships. The results highlight that the primary challenge hindering SME growth in Jakarta is limited capabilities, underscoring the need for more structured and targeted interventions. To address these constraints, strategic partnership initiatives involving government and private sector stakeholders should be tailored to meet the specific needs of MSMEs. Additionally, strengthening digital literacy is essential to enable SMEs to access broader market opportunities. The increasing reliance on social media and e-commerce platforms has emerged as a key digital literacy initiative among MSMEs, supporting their business expansion efforts.